Terapêutica e prescrição medicamentosa: conhecimento dos acadêmicos de Odontologia da cidade de Belém-Pará - SANTANA, Adan Lucas Pantoja de (2023)
Therapy and drug prescriptions are fundamental pillars of the formation of the Dental Surgeon and they are strategies used in order to control, prevent and / or treat diseases. The range medications range prescribed in the dental field is vast, making the global understanding of prescriptions and their influence on the patient's general health. Thus, the objective of this study is to assess the level of knowledge of students from public and private institutions, during and at the end of the graduation course. The research was cross-sectional and descriptive. Dentistry students from two educational institutions in the city of Belém-Pará who had recently completed the course of drug therapy and graduates who were in the last year/period of the Faculty of Dentistry were included in the study. After approval by the ethics committee and application of the informed consent, data were collected through a questionnaire with questions about general information from the participants and also related to: Pharmacology / Drug Therapy, current legislation regarding the practice of dental prescription and indication / common prescription and in special cases in the dental field. After statistical analysis of the data obtained, it was observed that in one of the institutions a large part of the interviewees had a poor (67%) or reasonable (28.9%) performance, while in the other evaluated institution this performance was statistically different with 44.2 % of participants with poor performance and 44.2% reasonable. The main deficiencies observed were in special prescriptions such as medical emergencies and fluoride prescriptions, where, respectively, only 7.8% and 13.3% of those evaluated had adequate knowledge. In view of the results found and limitations of the study, it is concluded that: the knowledge of dentistry students in the city of Belém-Pará is insufficient to carry out an adequate, safe and quality prescription, showing the need to readjust teaching-learning methodologies in drug therapy, including more sophisticated and dynamic approaches, with continuing education and constant theoretical-practical assessments throughout graduation.